Sehu: Dalang Wayang Potehi (布袋戲) di Jawa - Hirwan Kuardhani (Institut Seni Indonesia Yogyakarta, 2018)
Potehi is a hand-glove puppetry theatre art form, brought by the Chinese emigrant from Fujian in the sixteenth century. It used to be performed in their vessels (Jung-Jung) when they were docked. The Hokkian dialect was used at that time. As more Chinese immigrants settled down in Indonesia, they carried along the Potehi art in Java. Along the way, Potehi ceased to be performed in Hokkien dialect. Instead, it was Melayu Pasar or Melayu rendah (now Indonesian Language) being used, which was indeed the lingua franca among the Chinese community then. Nevertheless songs and poetry were still in Hokkian. Sehu called dalang Potehi. Was originally sehu as Hokkian true, a long the way sehu as Pranakan’s Tionghoa an than in this time sehu from etnic Java. The acculturation with the local society resulted in a very unique Potehi which was different from its original version. Potehi merupakan pertunjukan sarung tangan, yang dibawa para emigran China dari Fujian sekitar abad enam belas. Potehi biasanya dipertunjukkan di Jung-jung atau kapal-kapal mereka ketika sedang mendarat. Mereka menggunakan bahasa Hokkian dalam pertunjukannya. Ketika orang-orang Tionghoa menetap di Indonesia mereka membawa serta kesenian Potehi di Jawa. Pada perkembangannya pementasan Potehi tidak lagi menggunakan bahasa Hokkian melainkan menggunakan bahasa Melayu Pasar atau Melayu Rendah (sekarang bahasa Indonesia), bahasa yang sekaligus menjadi bahasa pengantar kaum Tionghoa saat itu. Walaupun untuk lagu dan syair masih memakai bahasa Hokkian. Sehu merupakan sebutan bagi dalang wayang Potehi. Awalnya sehu adalah orang Hokkian asli, pada perkembangannya adalah orang-orang Peranakan, dan saat ini sehu dari etnis Jawa. Proses akulturasi dengan penduduk setempat membuat pertunjukan Potehi menjadi unik dan berbeda dengan negeri asalnya.